Organisational Knowledge Management for Defect Reduction and Sustainable Development in Foundries - Cinzia Giannetti (International Journal of Knowledge and Systems Science, 2015)
Despite many advances in the field of casting technologies the foundry industry still incurs significant lossesdue to the cost of scrap and rework with adverse effects on profitability and the environment. Approachessuch as Six Sigma, DoE, FMEA are used by foundries to address quality issues. However these approacheslack support to manage the heterogeneous knowledge created during process improvement activities. Theproposed revision of ISO9001:2015 quality standard puts emphasis on retaining organisational knowledgeand its continual use in process improvement (ISO, 2014). In this paper a novel framework for creation,storage and reuse of product specific process knowledge is presented. The framework is reviewed taking intoconsideration theoretical perspectives of organisational knowledge management as well as addressing thechallenges concerning its practical implementation. A knowledge repository concept is introduced to demonstratehow organisational knowledge can be effectively stored and reused for achieving continual processimprovement and sustainable development.